Absolute and proportional measures of potential markers of rehearsal, and their implications for accounts of its development - Jarrold, Christopher; Danielsson, Henrik; Wang, Xiaoli (Frontiers in Psychology, 2015)
Previous studies of the development of phonological similarity and word length effects in children have shown that these effects are small or absent in young children, particularly when measured using visual presentation of the memoranda. This has often been taken as support for the view that young children do not rehearse. The current paper builds on recent evidence that instead suggests that absent phonological similarity and word length effects in young children reflects the same proportional cost of these effects in children of all ages. Our aims are to explore the conditions under which this a proportional scaling account can reproduce existing developmental data, and in turn suggest ways that future studies might measure and model phonological similarity and word length effects in children. To that end, we first fit a single mathematical function through previously reported data that simultaneously captures absent and negative proportional effects of phonological similarity in young children plus constant proportional similarity effects in older children. This developmental function therefore provides the benchmark that we seek to re-produce in a series of subsequent simulations that test the proportional scaling account. These simulations reproduce the developmental function well, provided that they take into account the influence of floor effects and of measurement error. Our simulations suggest that future empirical studies examining these effects in the context of the development of rehearsal need to take into account proportional scaling. They also provide a demonstration of how proportional costs can be explored, and of the possible developmental functions associated with such an analysis.